PENGARUH SUDUT DEFLEKSI GEAR TAB ELEVATOR TERHADAP STICK FORCE PILOT PADA PESAWAT N-219 - Pribadi, Dicki Hendri; Koekoeh KW, Robertoes; ., Sumarji; Syuhri, Ahmad; Rudi Sugara, Imam (STATOR: Jurnal Ilmiah Teknik Mesin, 2024)
Indonesia geographically is an archipelagic state that has been recognized by international community according to the PBB law of the sea then was ratified by Indonesia into UUD No.17 of 1985. The number of island in Indonesia currently according to BPS is 17.504 island, that makes Indonesia become the largest archipelagic country in the world and make potentially to have pioneer of aircraft. N-219 Aircraft produced by PT.Dirgantara Indonesia is a pioneer of aircraft that has been developed in Indoensia. Aircraft must meet the flight feasibility criteria to ensure flight safety. One of criteria is the value of a stick force pilot (FE), the force that the pilot receives to control the control surface of an aircraft. Regulation value of the stick force pilot reference is Civil Aviation Safety Regulation (CASR) part 23. The method used in this study is modelling the equations of the motion of the control surface balance tab with the elevator. This study seeks to find the optimum equation to meet the CASR23 regulation where the value of the stick force (FE) is ≤ 75 lbs. The result showed the optimum stick force pilot (FE) value in this modelling is equation III . In critical flight conditions the deflection of the balance tab is not enough to meet the design criteria, trim tab deflection (ẟtrim = 0 – 5˚) is used to reduce stick force pilot value and meets CASR23 regulation. In SLS condition all equation modelling meets the design criteria, where the maximum value stick force pilot (FE) is 51 lbs. keyword : stick force pilot, hinge moment, balance tab, trim tab, elevator.